Characterization of the complete mitochondrial genome and phylogenetic analysis of the common dolphin Delphinus delphis (Cetacea: Delphinidae). Issue 2 (3rd July 2018) - Lee, Kyunglee; Lee, JunMo; Cho, Yuna; Sohn, Hawsun; Choi, Young-Min; Lim, Se Ra; Kim, Hye Kwon; Yoon, Sun-Woo; Jeong, Dae Gwin; Kim, Ji Hyung
Abstract: We report the complete mitogenome of the common dolphin, Delphinus delphis . Overall structure of the 16, 387 bp mitogenome was very similar to those of other delphinid species, including the ancient D. delphis individuals. Multigene phylogeny revealed that D. delphis was most closely related to Stenella coeruleoalba, and clustered well with other species within the subfamily Delphininae.